Effects of Darkness and Light Spectra on Nutrients and Pigments in Radish, Soybean, Mung Bean and Pumpkin Sprouts - Linda Mastropasqua; Nunzio Dipierro; Costantino Paciolla (MDPI AG, 2020)
Fresh sprouts are an important source of antioxidant compounds and contain useful phytonutrients in the human diet. Many factors, such as the time of germination and types of light, influence the physiological processes and biosynthetic pathways in sprouts. The effect of red, blue and white light vs. dark conditions on the quality parameters in different sprout species after 5 d of germination was evaluated. Total ascorbate, soluble proteins, sugars, phenolic compounds, and pigments, such as carotenoids, chlorophylls, and anthocyanins, were investigated in radishes, soybeans, mung beans, and pumpkin sprouts. The light treatments increased the contents of vitamin C and the various pigments in all sprouts, conversely, they increased the soluble proteins and sugars, including d-glucose, d-fructose and sucrose, in soybeans and pumpkins, respectively. The dark treatment prevented the decrease in dry matter due to the lighting, while the red light induced an increase in polyphenols in soybean. These results suggest that the nutritional content of different sprouts grown under different light conditions depend on the dark or specific spectral wavelength used for their growth. The manuscript may increase the knowledge on light use for the industrialized food production aiming at preserving the phytonutrient content of vegetables, increasing the consumer health, or developing tailored diets for specific nutritional needs.